2019
DOI: 10.1155/2019/2142948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interventions with Manipulatives on Immediate Learning, Maintenance, and Transfer in Children with Mathematics Learning Disabilities: A Systematic Review

Abstract: Manipulatives are concrete or virtual objects (e.g., blocks and chips) often used in elementary grades to illustrate abstract mathematical concepts. We conducted a systematic review to examine the effects of interventions delivered with manipulatives on the learning of children with mathematics learning disabilities (MLD). The outcomes observed in the sample (N = 38) were learning, maintenance, and transfer in a variety of mathematical domains. Interventions using manipulatives were reported to be effective fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 71 publications
4
27
0
Order By: Relevance
“…There was a statistically significant average immediate effect of using VMs in mathematical accuracy from the baseline to the intervention phase. This finding is consistent with previous syntheses of research on mathematics manipulatives Lafay et al, 2019;Peltier et al, 2020) or technology-mediated interventions (Kiru et al, 2018;Ok et al, 2020) in the use of VMs, which have been found to be generally effective for improving the mathematical outcomes of students with disabilities. These previous research included VMs as a subset of targeted mathematics interventions and validated the positive effects of using mathematics manipulatives or technology-mediated mathematics interventions.…”
Section: The Immediate Effect and Trend During The Use Of Vmssupporting
confidence: 91%
See 3 more Smart Citations
“…There was a statistically significant average immediate effect of using VMs in mathematical accuracy from the baseline to the intervention phase. This finding is consistent with previous syntheses of research on mathematics manipulatives Lafay et al, 2019;Peltier et al, 2020) or technology-mediated interventions (Kiru et al, 2018;Ok et al, 2020) in the use of VMs, which have been found to be generally effective for improving the mathematical outcomes of students with disabilities. These previous research included VMs as a subset of targeted mathematics interventions and validated the positive effects of using mathematics manipulatives or technology-mediated mathematics interventions.…”
Section: The Immediate Effect and Trend During The Use Of Vmssupporting
confidence: 91%
“…Additionally, the use of VMs produced a significantly positive average trend during the intervention, indicating a growth over time due to the interventions incorporating VMs in their mathematics lessons. These findings add value to the existing syntheses and reviews on the effects of using VMs on students with disabilities Lafay et al, 2019;Peltier et al, 2020), particularly in terms of positive changes in trends and levels between the baseline and intervention phases.…”
Section: The Immediate Effect and Trend During The Use Of Vmsmentioning
confidence: 67%
See 2 more Smart Citations
“…Learning for students with disabilities can be conceptualized in four phases: acquisition, fluency, maintenance, and generalization (Shurr et al, 2019). However, researchers generally pay greater attention to the acquisition phase rather than the maintenance phase while teaching mathematics (Lafay et al, 2019; Spooner et al, 2012). Given the limited existing research in which maintenance effects of mathematics interventions have been examined, it is not clear whether the teaching practices determined to be an EBP for acquisition are also evidence-based for maintenance (Lafay et al, 2019).…”
Section: Maintenance In Mathematic Skillsmentioning
confidence: 99%